Conservação pós-colheita de cebola em função da adubação nitrogenada - França, Francisco Diorge de (Universidade Federal Rural do Semi-Árido, 2017)
In spite of the economic importance of the onion, little information is found regarding the effect of nitrogen fertilization on the variation of yield and quality attributes of this crop. Nitrogen as a macronutrient required by onion culture can influence productivity as well as bulb quality. In order to evaluate the effect of nitrogen fertilization on the post-harvest conservation of onion cultivars "IPA 11" and "Rio das Antas", an experiment was conducted at the Rafael Fernandes Experimental Farm of the Federal Rural Semi-Arid Federal University (UFERSA), located in the district of Lagoinha, rural area of the municipality of Mossoró-RN, from June to October 2016. The experimental design was a completely randomized design with four replications. The treatments were arranged in subdivided plots, the plots being represented by the nitrogen doses 0, 90, 180 and 225 kg ha-1 and the subplots the storage times, 0, 15, 30, 45 and 60 days, for each cultivar. The evaluated characteristics were: loss of mass, firmness, pungency, soluble solids, titratable acidity and the soluble solids / titratable acidity ratio. Nitrogen fertilization showed a significantly higher effect on the IPA 11 cultivar, where the lowest dose 0 kg h-1 of N allowed a greater loss of mass, firmness, pungency, soluble solids, titratable acidity, and a reduction of SS / AT over time of storage. In the cultivar Rio das Antas, there was no effect of the N doses for the characteristics loss of mass and soluble solids / titratable acidity. The 225 kg h-1 N dose reduced firmness, pungency and titratable acidity, on the other hand, promoted an increase in soluble solids contents.
Monografia
Keywords: Allium cepa L; Nitrogênio; Qualidade; Allium cepa L; Nitrogen; Quality; CIENCIAS AGRARIAS::AGRONOMIA